Patient safety culture among health care professionals in Saudi Arabia Hospital: review of the literature - Alharbi, Mohammed Fayez J; Soh, Kim Lam (Hampstead Psychological Associates, 2020)
Many advanced countries, like the United States of America, United Kingdom as well as Australia have dedicated the past few decades to the safety of lives by increasing the quality of research in the health sector, especially in-patient safety culture as a means towards achieving an improved health sector. Many people believe that Saudi Arabia’s health care system is among the best and safest medical care system in the world, but little research has been dedicated to unravel the practice of a safety culture existing within the care of health professionals in the hospital of the Saudi Arabia, as such, this research review the culture of safety literature within Saudi Arabia’s hospital setting.